ChemInform Abstract: Original Synthetic Route to Obtain a SrAl2O4 Phosphor by the Molten Salt Method: Insights into the Reaction Mechanism and Enhancement of the Persistent Luminescence. Issue 51 (December 2015) - Rojas‐Hernandez, Rocio Estefania; Rubio‐Marcos, Fernando; Goncalves, Ricardo Henrique; Rodriguez, Miguel Angel; Veron, Emmanuel; Allix, Mathieu; Bessada, Catherine; Fernandez, Jose Francisco
Abstract: The formation mechanism of SrAl2 O4 in a molten salt synthesis is systematically investigated by DSC‐TG‐DTG, in‐situ XRD, and Raman spectroscopic analyses.